Plotinus, Porphyry and Iamblichus philosophy and religion in Neoplatonism - Smith, Andrew 1945- (Ashgate Variorum, 2011)
These essays are devoted to Neoplatonism and especially to Plotinus and Porphyry. They deal with Plotinus' development of the Platonic forms, and include a lengthy assessment of Porphyry's contribution to the Platonic tradition
Keywords: Plotinus -- 205-270; Porphyrius -- 233-301; Iamblichus -- Chalcidensis -- 250-325; Neuplatonismus; Aufsatzsammlung